2015
DOI: 10.1128/mcb.00184-15
|View full text |Cite
|
Sign up to set email alerts
|

Group IVA Cytosolic Phospholipase A2 Regulates the G2-to-M Transition by Modulating the Activity of Tumor Suppressor SIRT2

Abstract: The G 2 -to-M transition (or prophase) checkpoint of the cell cycle is a critical regulator of mitotic entry. SIRT2, a tumor suppressor gene, contributes to the control of this checkpoint by blocking mitotic entry under cellular stress. However, the mechanism underlying both SIRT2 activation and regulation of the G 2 -to-M transition remains largely unknown. Here, we report the formation of a multiprotein complex at the G 2 -to-M transition in vitro and in vivo. Group IVA cytosolic phospholipase A 2 (cPLA 2 ␣)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Another possibility is that silencing cPLA2 in the bone marrow causes intrinsic changes in the leukocytes that affect their ability to hone to the injured kidney independent of downstream eicosanoid expression. cPLA2 is known to have several noncanonical functions most recently implicated in controlling proliferation and cell cycle turnover (24,25). We did not examine cell proliferation or apoptosis in our current studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that silencing cPLA2 in the bone marrow causes intrinsic changes in the leukocytes that affect their ability to hone to the injured kidney independent of downstream eicosanoid expression. cPLA2 is known to have several noncanonical functions most recently implicated in controlling proliferation and cell cycle turnover (24,25). We did not examine cell proliferation or apoptosis in our current studies.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are expressed throughout the nephron (19,20) and their products mediate a host of physiologic and pathologic processes in animal models of renal disease (21)(22)(23). We have shown that cPLA2 expression in human renal tubular epithelial cells promotes epithelial dedifferentiation and proliferation (24), and others have implicated cPLA2 in the control of the G2-M cell cycle checkpoint (25). These biological effects could be sufficient to modify renal injury and fibrosis, given the importance of tubular epithelial damage in renal fibrinogenesis (26,27).…”
mentioning
confidence: 99%
“…Expression of SIRT2, which is involved in the regulation of microtubule dynamics 8,10 , is regulated in a cell cycle-dependent manner where SIRT2 localizes to centrosomes and the mitotic spindle 62 . Phosphorylation of SIRT2 by cyclin A-CDK2 reduces binding of SIRT2 to centrosomes and promotes G2/M progression 63 . In line with this, increased SIRT2 levels due to mitotic stress cause an extension of the mitotic phase 64 presumably through the regulatory role of SIRT2 towards the anaphase promoting factor/cyclosome (APC/C) and hence cyclin B1 degradation 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Published data has demonstrated that cPLA 2 α directly regulates mitotic entry through the G2/M checkpoint through its interaction with the tumor suppressor gene SIRT2. (18) Additionally, cPLA 2 α may play a role in intracellular membrane trafficking. (17) Unfortunately, there is limited data regarding the role of cPLA 2 α in non-transformed epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accumulating evidence supports that cPLA 2 α itself, independent of its canonical functions, may play fundamental roles in membrane trafficking and cellular proliferation. (17, 18)…”
Section: Introductionmentioning
confidence: 99%